Investigating factors that contribute to the ability of Staphylococcus aureus to colonise atopic dermatitis skin - TOWELL, AISLING (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2019)
The skin of atopic dermatitis (AD) patients is frequently colonised by Staphylococcus aureus. Colonisation by S. aureus correlates with disease severity and exacerbated disease symptoms. The factors involved in S. aureus colonisation of AD skin have not been fully described. This thesis aimed to identify molecular determinants contributing to the colonisation of AD skin by S. aureus. A skin protein corneodesmosin (CDSN) is abnormally displaced in AD skin and is potentially more accessible to bacteria. Here, CDSN was identified as a novel ligand for S. aureus. A plasmid expressing GST-tagged recombinant CDSN (rCDSN) was constructed and rCDSN was purified from bacteria. Allelic exchange was used to construct mutants of a clinically relevant AD strain AD08, deficient in ClfB and/or FnBPA and/or FnBPB to examine the role of these proteins. AD08 did not adhere to CDSN in the absence of ClfB and FnBPB indicating that these two proteins promote adherence to CDSN. Measuring S. aureus adherence to corneocytes isolated from AD patients showed that ClfB, FnBPA and/or FnBPB facilitate attachment to AD corneocytes. The S. aureus binding site in CDSN was mapped to the N-terminal omega loop region and blocking this region with anti- CDSN antibody raised against the N-terminus of CDSN reduced S. aureus adherence to AD corneocytes implying that S. aureus targets CDSN to adhere to AD corneocytes. Having shown that FnBPA and FnBPB bind to CDSN in vitro, the ability of these proteins to support bacterial adhesion to loricrin and cytokeratin 10 (K10) was examined. Both proteins are established ligands for ClfB however this study showed that S. aureus mutants deficient in FnBPA and/or FnBPB had reduced adherence to both ligands. Furthermore, overexpressing either FnBPA or FnBPB from a plasmid promoted bacterial adherence, indicating that both proteins are capable of binding to loricrin and K10 independently. S. aureus strains of clonal complex (CC) 1 are frequently isolated from AD patients and the factors contributing to CC1 persistence in AD skin are unknown. Here, it was shown that a panel of CC1 strains from AD (ADCC1) adhered more strongly to CDSN than commensals isolated from the nasal cavity of healthy children. CC30 strains are prevalent commensals of the nose of the healthy population. Three S. aureus ADCC1 strains, and two CC30 commensal strains were labelled with antibiotic resistance genes and competitive growth assays were carried out to determine whether ADCC1 strains have a competitive advantage over CC30 strains. Two of the three ADCC1 strains outcompeted growth of both CC30 isolates. Likely, the ability of ADCC1 strains to adhere strongly to CDSN in AD skin gives them a competitive advantage where they can then proliferate and outcompete other S. aureus isolates, to dominate the AD skin environment.
APPROVED
Keywords: Staphylococcus aureus; Atopic Dermatitis; Microbiology; Skin disease